Anti-mycobacterial and anti-inflammatory activity of restinga plants: a dual approach in searching for new drugs to treat severe tuberculosis - Araujo,Marlon Heggdorne de (2021)
Abstract Tuberculosis (TB) still constitutes a threat to public health in various regions of the world. The existing treatment is long and has many side effects. The need to identify new anti-TB compounds and also adjuvants to control exacerbated inflammation in severe TB cases is relevant. Therefore, the objective of this study was to evaluate the anti-mycobacterial activity of extracts and fractions in vitro from plant species collected in the Restinga of Jurubatiba, in Rio de Janeiro state, Brazil. In addition, to verify their immunomodulatory action and cytotoxicity on macrophages. The dichloromethane fraction of Kielmeyera membranacea and Eremanthus crotonoides showed the lowest MIC50 against Mycobacterium bovis BCG (0.95 ± 1.08 and 2.17 ± 1.11 μg/mL, respectively) and M. tuberculosis H37Rv (4.38 ± 1.19 and 15.28 ± 1.21 μg/mL, respectively). They were also able to inhibit the NO and TNF-α production in LPS-stimulated macrophages, without being toxic to cells. Using gas chromatography analysis coupled with mass spectrometer it was possible to suggest the presence of fatty acids and terpenes in the most promising fractions. Those compounds have been described for their anti-mycobacterial activity. These results have enabled identifying Kielmeyera membranacea and Eremanthus crotonoides as the most promising studied species in searching for new anti-TB compounds with dual activity.